2018
DOI: 10.1097/md.0000000000012750
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endostar combined with chemotherapy in advanced well-differentiated pancreatic neuroendocrine tumors

Abstract: The aim of the present study was to assess the effect of Endostar and temozolomide or dacarbazine plus 5-fluorouracil (5-FU) in patients with advanced pancreatic neuroendocrine tumors (pNETs).Phase II study of 14 patients with locally advanced or metastatic well-differentiated pNETs treated between April 2013 and September 2016. Patients received temozolomide or dacarbazine plus 5-FU, and Endostar. The primary outcome was the radiographic response rate.All 14 patients had nonfunctional pNETs. Six patients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Endostar is generally dosed at 7.5 mg/m 2 /day for 14 consecutive days (13,16). However, clinical trials have evaluated different doses, including 15 mg/day for 14 days or 45 mg/day on days 1, 3, and 4 (35,36). In the present study, a treatment regimen of 15 mg daily for 7 days was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Endostar is generally dosed at 7.5 mg/m 2 /day for 14 consecutive days (13,16). However, clinical trials have evaluated different doses, including 15 mg/day for 14 days or 45 mg/day on days 1, 3, and 4 (35,36). In the present study, a treatment regimen of 15 mg daily for 7 days was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…A real-world study of 88 patients with sensitizing mutation negative NSCLC showed that Endostar combined with platinum-based doublet chemotherapy improved survival, but at the cost of higher occurrence of AEs [20]. A real-world study of 14 patients with pancreatic neuroendocrine tumors showed that the most common grade 1-2 AEs were neutropenia (43%) and leucopenia (21%) [21]. A real-world study of 23 patients with advanced mucosal melanoma showed that the most common severe AEs of Endostar with chemotherapy were leucopenia (13%), thrombocytopenia (13%), anemia (4%), nausea and vomiting (4%), and elevated transaminase (4%) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer patients with subsequent liver metastasis are extensively studied, and several phase II clinical trials are using recombinant endostatin (either alone or combined with other drugs) as an anti-tumour agent [ 221 , 222 , 223 ]. In addition, the effect of endostatin in advanced well-differentiated pancreatic neuroendocrine tumours is being tested [ 224 ].…”
Section: Heparan Sulfate Clinical Applications–recent Advancesmentioning
confidence: 99%